Design and Development of a Wideband Planar Yagi Antenna Using Tightly Coupled Directive Element - Muhammad A. Ashraf; Khalid Jamil; Ahmed Telba; Mohammed A. Alzabidi; Abdel Razik Sebak (Micromachines, 2020)
In this paper, a novel concept on the design of a broadband printed Yagi antenna for S-band wireless communication applications is presented. The proposed antenna exhibits a wide bandwidth (more than 48% fractional bandwidth) operating in the frequency range 2.6 GHz–4.3 GHz. This is achieved by employing an elliptically shaped coupled-directive element, which is wider compared with other elements. Compared with the conventional printed Yagi design, the tightly coupled directive element is placed very close (0.019λ to 0.0299λ) to the microstrip-fed dipole arms. The gain performance is enhanced by placing four additional elliptically shaped directive elements towards the electromagnetic field’s direction of propagation. The overall size of the proposed antenna is 60 mm × 140 mm × 1.6 mm. The proposed antenna is fabricated and its characteristics, such as reflection coefficient, radiation pattern, and gain, are compared with simulation results. Excellent agreement between measured and simulation results is observed.